Academic development, SoTL and educational research. Issue 2 (2nd April 2016) - Geertsema, Johan
Abstract: This essay considers the relation between academic development, the scholarship of teaching and learning, and educational research. It does so with reference to questions of academic identity and disciplinary expertise, arguing that as developers we need to consider carefully the ways in which we frame how we approach attempts to foster reflective practice through the scholarship of teaching and learning. Rather than positioning SoTL as educational research, it may make more sense to approach it strategically as a means of development oriented towards more local levels of practice.